Primary Pulmonary Hodgkin’s Lymphoma - R Lluch-Garcia; A Briones-Gomez; E Monzó Castellano; F Sanchez-Toril; A Lopez; B Brotons (Canadian Respiratory Journal)
A 21-year-old man presented to hospital with a two-month history of productive cough with no other symptoms. Radiology revealed a cavitating lesion in the left upper lobe for which a variety of diagnoses were considered. A biopsy revealed primary pulmonary Hodgkin’s lymphoma. Primary pulmonary Hodgkin’s lymphoma is an uncommon initial presentation; lung lesions usually occur later in the course of the disease. Following diagnosis, the patient began chemotherapy and full remission was achieved.